Protecting the trunnion during isolated acetabular component revision total hip arthroplasty: a technical note. Issue 2 (March 2017) - Shemesh, Shai; Velkes, Steven; Kosashvili, Yona; Cohen, Nir
Abstract : Corrosion at the trunnion-taper junction of the femoral component in total hip arthroplasty has been identified as a potential concern. Failure of the trunnion-taper junction can be initiated by surface micromotions caused by surface contamination. This technique is to be used in cases of isolated acetabular component revision total hip surgeries. Since the prosthetic head is removed during revision of the acetabular component to optimize exposure, the trunnion remains exposed in the surgical field and, therefore, is subjected to scratching and intimate contact with surgical instruments and accumulation of biologic debris. Use of a plastic sleeve protects the trunnion against intraoperative scratching and contamination.